Association between patterns of eating habits and mental health problems in Chinese adolescents: A latent class analysis - Li, Xiaotong; Sun, Mengzi; Yao, Nan; Liu, Jiaqi; Wang, Ling; Hu, Wenyu; Yang, Yixue; Guo, Ruirui; Li, Bo; Liu, Yajuan (Frontiers in Nutrition, 2022)
Objective: We aimed to investigate the association between different eating habit patterns and mental health problems among Chinese middle and high school students, and further to estimate the interaction effect of different grouping variables on eating habits. Methods:1348 adolescents from Jilin Province in China were involved in this cross-sectional study. Mental health and eating habits were assessed using General Health Questionnaire and questions on Nutrition Knowledge, Attitude and Practice, respectively. Latent class analysis (LCA) was performed to identify eating habit patterns. Binary logistic regression and generalized linear models were used to explore the association between eating habit patterns, energy-adjusted nutrient intakes and mental health problems. Interaction analysis was performed to analyze the association between eating habits and mental health in different groups. Results: Based on the LCA results, a 3-class parallel model was identified: 648 adolescents (48.1%) were classified in class-1 “Healthy Eating Behavior/Eating at Home”, 452 adolescents (33.5%) in class-2 “Healthy Eating Behavior/Eating at School” and 248 adolescents (18.4%) in class-3“Unhealthy Eating Behavior/Random Place”. Compared with class-1, participants in class-2 and class-3 were at higher risk of mental health problems, especially for class-3 (p<0.05). The energy and nutrient intakes by different latent classes showed that adolescents who ate unhealthy had lower daily intake of energy, protein, carbohydrate, fiber, Vitamins and minerals (p<0.05). The interaction between age, sleep duration and different eating habits was statistically significant (p for interaction<0.1). Conclusion: “Unhealthy eating behavior/random place pattern” was positively correlated with mental health problems of adolescents. The adolescents with health diet were accompanied by fewer mental health problems, especially for that eating at home. And there were interactions between eating habits and age, sleep duration on the mental health problems.